Developments in evidence creation for treatments of inborn errors of metabolism. Issue 1 (4th October 2020) - Stockler‐Ipsiroglu, Sylvia; Potter, Beth K.; Yuskiv, Nataliya; Tingley, Kylie; Patterson, Marc; van Karnebeek, Clara
Abstract: Inborn errors of metabolism (IEM) represent the first group of genetic disorders, amenable to causal therapies. In addition to traditional medical diet and cofactor treatments, new treatment strategies such as enzyme replacement and small molecule therapies, solid organ transplantation, and cell‐and gene‐based therapies have become available. Inherent to the rare nature of the single conditions, generating high‐quality evidence for these treatments in clinical trials and under real‐world conditions has been challenging. Guidelines developed with standardized methodologies have contributed to improve the practice of care and long‐term clinical outcomes. Adaptive trial designs allow for changes in sample size, group allocation and trial duration as the trial proceeds. n‐of‐1 studies may be used in small sample sized when participants are clinically heterogeneous. Multicenter observational and registry‐based clinical trials are promoted via international research networks. Core outcome and standard data element sets will enhance comparative analysis of clinical trials and observational studies. Patient‐centered outcome‐research as well as patient‐led research initiatives will further accelerate the development of therapies for IEM.